2009
DOI: 10.1007/s10763-009-9161-3
|View full text |Cite
|
Sign up to set email alerts
|

Variable Relationships Among Different Science Learners in Elementary Science-Methods Courses

Abstract: Due to a technical error, the name and address of the second author has been deleted during the production of the article. The names of the authors should read:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Our experience also confirmed studies (e.g., Feistritzer and Boyer, 1983;Bleicher, 2009) that show many ElEd FIGURE 4: Exam score and year of study for Semester 1 (F11). The exam scores for first-year students (Y1) are compared with those of more senior students (Y2/Y3/Y4).…”
Section: Challenges and Lessons Learnedsupporting
confidence: 89%
See 1 more Smart Citation
“…Our experience also confirmed studies (e.g., Feistritzer and Boyer, 1983;Bleicher, 2009) that show many ElEd FIGURE 4: Exam score and year of study for Semester 1 (F11). The exam scores for first-year students (Y1) are compared with those of more senior students (Y2/Y3/Y4).…”
Section: Challenges and Lessons Learnedsupporting
confidence: 89%
“…Research on elementary teachers demonstrated that a majority possessed a negative attitude towards science (e.g., Feistritzer and Boyer, 1983;Pedersen and McCurdy, 1992;Bleicher, 2009) and that such negative attitudes were passed onto young learners (e.g., Scharmann and Orth Hampton, 1995 The final design of the online part of the course is illustrated by the schematic shown in Fig. 1.…”
Section: Development Of the Online Component Content Experts Meet Curmentioning
confidence: 99%
“…Understanding the factors that may affect science teaching self‐efficacy during preservice teacher preparation programs is important because of the previously stated implications for teacher behavior. As a result, many studies on preservice teacher science teaching self‐efficacy exist, but primarily focus on the impact of courses within preservice programs, such as science methods courses and student teaching, on science teaching self‐efficacy (Bautista, ; Bleicher, , ; Bleicher & Lindgren, ; Bursal, ; Cantrell, ; Gunning & Mensah, ; Hechter, ; King & Wiseman, ; McDonnough & Matkins, ; Morrell & Carroll, ; Mulholland, Dorman, & Odgers, ; Palmer, 2006a; Schoon & Boone, ; Tosun, 2000b; Utley, Moseley, & Bryant, ).…”
mentioning
confidence: 99%
“…There are numerous examples of studies investigating the science teaching self-efficacy gains of preservice ISSN 1648-3898 teachers with standard pretest-posttest research designs (Bleicher, 2009;Bleicher & Lindgren, 2005;Bursal, 2008;Ginns et al, 1995;Ginns & Watters, 1999;Huinker & Madison, 1997;Morrell & Carroll, 2003;Palmer, 2006aPalmer, , 2006bPlourde, 2002;Richardson & Liang, 2008;Soprano & Yang, 2013;Utley et al, 2005;Yılmaz & Huyugüzel-Çavaş, 2008), but no study -except Cantrell (2003) and Hechter (2011) -is located in the literature using retrospective tests to measure the same construct. Also, it is not investigated that whether the differences between the standard and retrospective test scores are seen in samples from different contexts.…”
Section: Introductionmentioning
confidence: 99%